Answer:
![x=513 \Rightarrow S=\{513\}](https://img.qammunity.org/2021/formulas/mathematics/college/iei4keug1eornvf2cshuos05b7ms9tynji.png)
Explanation:
1) Rewriting for the sake of clarity:
![(x-1)^{(2)/(3)}=64](https://img.qammunity.org/2021/formulas/mathematics/college/skskosixxp2oazhwss9f4mrod5gmbqoztu.png)
2) To solve it, we need to turn the rational exponent equal to 1 via exponent rule of product. Multiplying 2/3 by its reciprocal 3/2 we get 1, since this is an equality we need to do it on the other side.
![(x-1)^{(2)/(3)}=64\\\\((x-1)^{(2)/(3)}]^{(3)/(2)}=(64)^{(3)/(2)}\\(x-1)=\sqrt{64^(3)}\\x-1+1=512+1\\x=513](https://img.qammunity.org/2021/formulas/mathematics/college/6ptjwbo4lbmjo4zzd3zo8is66ot92jbj9a.png)